Analisis Kepentingan Dan Kinerja (IPA) Dari Benih Kentang Varietas Baru “X” - Suminartika, Eti; Putra, Ivangga Dwi; Setiawan, Iwan; Sukayat, Yayat (Universitas Galuh, 2024)
ABSTRACTPotato imports for industrial raw materials tend to increase, this is due to the lack of domestic potato production (industrial raw materials) is relatively small, the lack of industrial potato production can be caused by the lack of supply of seed potatoes (industrial raw materials) from local breeders. The lack of industrial seed potato supply has led to the emergence of new varieties of seed potato (for industry). New seed potato varieties are generally untested by consumers. This study was conducted to compare new potato varieties”X” and Atlantis varieties and analyze the level of importance and performance of new potato seed varieties by consumers. The research was conducted using a quantitative design. The sample was taken using snow ball sampling, the research was conducted in Bandung district, West Bandung district and Garut district in February 2023. Data were analyzed by descriptive analysis and Importance-Performance Analysis (IPA). Results show: There are eight attributes of new potato seed varieties, namely the number of sprouting eyes, resistance to pests and diseases, harvest age, tuber size, tuber shape, color and texture of tuber flesh, storability and productivity levels. The advantages of new potato seed varieties “X” over Atlantis potato seed varieties (the dominant variety planted by farmers) are that they have higher productivity potential and the harvesting age can be shorter. Another advantage of the new potato seed varieties is that they have high productivity potential and good taste so that they can be processed into various kinds of processed products such as French fries and chips. Attributes that are important to farmers (seed consumers) and perform well in new potato seed varieties “X” are tuber size and harvesting age. Attributes that need to be improved from the new seed potato varieties are pest-disease resistance and maintaining productivity.